Vildagliptin Reduces Stenosis of Injured Carotid Artery in Diabetic Mouse Through Inhibiting Vascular Smooth Muscle Cell Proliferation via ER Stress/NF-κB Pathway - Ji, Yuqin; Ge, Yingbin; Xu, Xinyu; Ye, Sen; Fan, Yuansheng; Zhang, Jing; Mei, Lianlian; Zhang, Xiaofeng; Ying, Lianghong; Yang, Tao; Li, Chunjian (Frontiers in Pharmacology, 2019)
Dipeptidyl peptidase-4 (DPP-4) inhibitors are novel anti-hyperglycemic drugs for type 2 diabetes. It has been reported that DDP-4 inhibitor could exert pleiotropic effects on cardiovascular system. This study was to explore the effect and mechanism of vildagliptin on the stenosis of injured carotid artery in diabetic mouse. Twenty six-week-old male db/db mice (BKS) were randomized into vildagliptin treated and vehicle control groups. Ligation injury was first performed in left carotid arteries of all diabetic mice, then oral vildagliptin or equal amount of PBS was correspondingly administered to the mice from the next day to ligation injury for 4 weeks. Effects on proliferation were detected via histological and morphometric analysis. Endoplasmic reticulum (ER) stress and nuclear factor kappa B (NF-κB) markers were determined by immunoblot analysis. After 4 weeks of vildagliptin delivery, it was observed that the intimal area and neointimal thickness of the ligated carotid arteries were significantly reduced as compared to the control group. In vivo, vildagliptin suppressed the expressions of PCNA and α-SMA, phospho-p65, phospho-IKKα/β, GRP78 and CHOP, as well as IRE-1 in vascular smooth muscle cells (VSMCs). In vitro, the proliferation and hypertrophy of VSMCs were significantly inhibited by blocking the IRE-1 pathway, and the inhibition of phospho-IRE-1 expression down-regulated the expression of phospho-IKKα/β in VSMCs. Vildagliptin reduced the stenosis of injured carotid arteries in diabetic mice, and this effect was achieved via inhibiting the activation of ER stress/NF-κB pathway.